Hubungan Higiene dan Perilaku Rumah Tangga dengan Kepadatan Tikus di Permukiman Rawan Banjir Desa Sidomulyo, Kabupaten Lamongan - Feby Hidayah Pratama; Nur Lathifah Syakbanah; Rizky Rahadian Wicaksono; Muhammad Hanif (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
The presence of rats in residential areas is an environmental health problem because it has the potential to transmit various diseases. Poor household hygiene and household behavior that does not support environmental hygiene can increase the risk of rat presence. This risk is even greater in flood-prone settlements because flooding can disrupt rat habitats and encourage them to migrate to residential areas in search of safer places. This study aims to analyze the relationship between hygiene vulnerabilities and household behavior with rat density in flood-prone settlements in Sidomulyo Village, Deket District, Lamongan Regency. This study used a quantitative analysis method with a cross-sectional design. A sample of 40 houses was selected using a purposive sampling technique, with 160 sticky traps installed for 2 nights inside and outside the houses. Data were collected through observation and questionnaires, then analyzed using the chi-square test and logistic regression. The results showed a trap success rate of 61.25%, indicating a high rat density. The most influential household hygiene and behavior variables included the habit of cleaning wastewater treatment plants (p=0.018; OR=0.053), the habit of hoarding items (p=0.030; OR=0.066), and holes/gaps in the house (p=0.011; OR=0.173). These results indicate that the rat density in Sidomulyo Village is relatively high and is influenced by hygiene and household behavior factors. Therefore, improving environmental sanitation and implementing clean living behaviors are needed to reduce the presence of rats in residential areas